2012
DOI: 10.2166/wh.2012.208
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrocatalytic disinfection of water and wastewater: performance evaluation by qPCR and culture techniques

Abstract: Photoelectrocatalytic oxidation (PEC) was evaluated as a disinfection technique using water and secondary treated wastewater spiked with Escherichia coli and Enterococcus faecalis. PEC experiments were carried out using a TiO(2)/Ti-film anode and a zirconium cathode under simulated solar radiation. Bacterial inactivation was monitored by culture and quantitative polymerase chain reaction (qPCR). Inactivation rates were enhanced when the duration of the treatment was prolonged and when the bacterial density and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…55 Previous work has demonstrated that under the same conditions Gram-negative bacteria take significantly longer to be de-activated than Gram-positive. 56 We suggest that the BTO-TiO 2 system affects rapid deactivation of E. coli, but would warn against assuming such efficient bactericidal action against other micro-organisms.…”
Section: Bactericidal Testingmentioning
confidence: 91%
See 1 more Smart Citation
“…55 Previous work has demonstrated that under the same conditions Gram-negative bacteria take significantly longer to be de-activated than Gram-positive. 56 We suggest that the BTO-TiO 2 system affects rapid deactivation of E. coli, but would warn against assuming such efficient bactericidal action against other micro-organisms.…”
Section: Bactericidal Testingmentioning
confidence: 91%
“…It can be concluded that BTO is acting in this capacity as an electron sink, similarly to the traditional model of electron transfer on P25. 56 Given that removal of oxygen from a test solution somewhat abated the photocatalytic efficiency however, it can be concluded that not all photoexcited electrons in the anatase conduction band are transferred to BTO/rutile, and that some electrons are trapped as superoxide ions.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Considering that the major groups of pathogenic organisms are: (a) bacteria, (b) viruses, (c) protozoans and (d) helminths ( Sperling, 2008 ) it is important to point out that the initial microorganism density as well as the nature of mixed bacterial populations in water play an important role in the selection of a disinfection process, since the combination affects the type, cost and required treatment time for complete microbial inactivation ( Venieri et al, 2012 , 2013 ). In this regard for example, while bacteria are physically protected at high population density values, suspended solids and turbidity can decrease the performance of the photo-assisted EAOPs due to irregular light intensity scattering ( Rather and Lo, 2020 ).…”
Section: Infectious Agents Commonly Found In Water and Wastewatermentioning
confidence: 99%
“…In Eq. (2) the subscripts cb and vb denote the conduction and valence bands, respectively ( Domínguez-Espíndola et al., 2019 ; Venieri et al., 2013 ).…”
Section: Direct Oxidationmentioning
confidence: 99%
“…Genomic DNA was extracted performing chemical lysis and phenol/chloroform/isoamyl alcohol (25:24:1) extraction using lysozyme and proteinase K, according to our previous work (Venieri et al, 2013 quantity and purity of all DNA samples were determined measuring their absorbance at 260 nm and estimating the ratio of absorbance values at 260 nm and 280 nm, respectively.…”
Section: Analytical and Molecular Biology Techniquesmentioning
confidence: 99%